2016
DOI: 10.1007/s12035-016-9912-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-744 and miR-224 Downregulate Npas4 and Affect Lineage Differentiation Potential and Neurite Development During Neural Differentiation of Mouse Embryonic Stem Cells

Abstract: Neuronal PAS domain protein 4 (Npas4) is a brain-specific transcription factor whose expression is enriched in neurogenic regions of the brain. In addition, it was demonstrated that Npas4 expression is dynamic and highly regulated during neural differentiation of embryonic stem cells (ESCs). While these findings implicate a role for Npas4 in neurogenesis, the underlying mechanisms of regulation remain unknown. Given that growing evidence suggests that microRNAs (miRNAs) play important roles in both embryonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Here, we found miR-744 was lower in severe asthma, showing great promise for treatment of severe asthma. miR-744 has been reported to play essential roles in renal inflammation [27], neural differentiation [28], and cell proliferation [29]. Importantly, we showed that miR-744 limited the proliferation rate of bronchial epithelial cells in severe asthma.…”
Section: Discussionmentioning
confidence: 55%
“…Here, we found miR-744 was lower in severe asthma, showing great promise for treatment of severe asthma. miR-744 has been reported to play essential roles in renal inflammation [27], neural differentiation [28], and cell proliferation [29]. Importantly, we showed that miR-744 limited the proliferation rate of bronchial epithelial cells in severe asthma.…”
Section: Discussionmentioning
confidence: 55%
“…Due to their extraordinary neurochemical and functional diversity, GABAergic neurons are involved in various neuropsychiatric disorders, such as epilepsy, anxiety, autism, and other pathological processes, such as cerebral ischemia injury and drug addiction. Neurogenesis requires precisely regulated patterns of gene expression in which positive and negative signals must be balanced to generate the correct cell types at the appropriate developmental period (Choy et al, 2017). The development and differentiation of GABAergic neurons are complex processes that involve the interaction of a series of genes that regulate each other in an orderly manner.…”
Section: Discussionmentioning
confidence: 99%
“…Npas4 is an inducible transcription factor (ITF) that is expressed exclusively in neurons and is selectively activated by neuronal activity rather than by extracellular stimuli, such as growth factors and neurotrophic factors. Npas4 belongs to the bHLH PAS protein family and is an important target for regulating stress responses (Choy et al, 2017; Moser et al, 2004). As a transcription factor, Npas4 exerts its biological function by controlling the expression of downstream transcription targets.…”
Section: Formation Of Synapses In Gabaergic Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mir-186 controls the surface expression of GluA2 (ionic glutamate receptor A2) in hippocampal neurons (Silva MM et al, 2019). Down-regulated miR-744 could downregulate Npas4 as an intrinsic regulator of seizures and epilepsy (Choy FC et al, 2017;Shan W et al, 2018). Together, these alterations represent an intrinsic therapeutic mechanism of LF-rTMS for epilepsy.…”
Section: Discussionmentioning
confidence: 99%